Opioid Use After Intensive Care: A Nationwide Cohort Study. Issue 3 (29th January 2021) - von Oelreich, Erik; Eriksson, Mikael; Sjölund, Karl-Fredrik; Discacciati, Andrea; Larsson, Emma; Oldner, Anders
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVE: To describe opioid use after ICU admission, identify factors associated with chronic opioid use after critical care, and determine if chronic opioid use is associated with an increased risk of death. DESIGN: Retrospective cohort study. SETTING: Sweden including all registered ICU admissions between 2010 and 2018. PATIENTS: Adults surviving the first two quarters after ICU admission were eligible for inclusion. A total of 265, 496 patients were screened and 61, 094 were ineligible. INTERVENTIONS: Admission to intensive care. MEASUREMENTS AND MAIN RESULTS: Among 204, 402 individuals included in the cohort, 22, 138 developed chronic opioid use following critical care. Mean opioid consumption peaked after admission followed by a continuous decline without returning to baseline during follow-up of 24 months. Factors associated with chronic opioid use included high age, female sex, presence of comorbidities, preadmission opioid use, and ICU length of stay greater than 2 days. Adjusted hazard ratio for death 6–18 months after admission for chronic opioid users was 1.7 (95% CI, 1.6–1.7; p < 0.001). In the subset of patients not using opioids prior to admission, similar findings were noted. CONCLUSIONS: Mean opioid consumption is increased 24 months after ICU admission despite the lack of evidence for long-term opioid treatment. Given the high number of ICU entries and risk of excess mortality for chronic users, preventing opioid misuse is important when improving long-term outcomes after critical care.